Does anti-reflux surgery disrupt the pathway of Barrett’s esophagus progression to cancer? - Schoppmann, Sebastian F.; Kristo, Ivan; Riegler, Martin (Translational Gastroenterology and Hepatology, 2018)
In patients with Barrett’s esophagus (BE), anti-reflux surgery aims to sustainable control reflux symptoms and heal reflux induced esophageal mucosal inflammation and prevent progression of BE to adenocarcinoma. There is growing evidence that beside gastric acid, bile salts in refluxed duodenal juice are responsible for the development and progression of BE. However, the pathogenesis of BE progression and the metaplasia-dysplasia-carcinoma sequence of the adenocarcinoma of the esophagus (EAC) is multifactorial and occurs over long natural time course. After anti-reflux surgery significant levels of regression from metaplastic Barrett’s to non-metaplastic epithelium as well as from dysplastic to non-dysplastic BE have been observed and a randomized trial showed that sufficient surgical reflux control reduces the risk of Barrett’s progression significantly when compared to medical treatment. Thus, large cohort studies show significant reduced risk of EAC in patients suffering from gastroesophageal reflux disease (GERD) with and without BE after anti-reflux surgery. Even after anti-reflux surgery the risk for EAC remains elevated in patients with BE and the right moment of intercepting the progressive nature of GERD has to be discussed in future. The paper also addresses the impact of anti-reflux surgery, endoscopic ablation and life style therapies for the management of GERD, BE and cancer prevention.